2010
DOI: 10.1093/intimm/dxq059
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effects of anti-Dll4 mAb on Theiler's murine encephalomyelitis virus-induced demyelinating disease

Abstract: We examined the role of Notch ligand Delta-like 4 (Dll4) in the development of Theiler's murine encephalomyelitis virus (TMEV)-induced demyelinating disease (TMEV-IDD). Treatment with mAb to Dll4, especially during the effector phase, resulted in significant suppression of the disease development both clinically and histologically. The number of infiltrating mononuclear inflammatory cells in the spinal cords was also decreased in mice treated with anti-Dll4 mAb. Semi-quantitative analysis of mRNA by using real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…DLL4- blocking mAbs suppress disease in models of multiple sclerosis, graft-versus-host disease, and transplantation (Takeichi et al, 2010; Tran et al, 2013; Ishida et al, 2011). Based on our findings that CD4 + T cell responses were impaired in the absence of DLL4 on APCs, we posit that the immune-suppressive effects of DLL4 mAb in these models were due to less-efficient T cell priming.…”
Section: Discussionmentioning
confidence: 99%
“…DLL4- blocking mAbs suppress disease in models of multiple sclerosis, graft-versus-host disease, and transplantation (Takeichi et al, 2010; Tran et al, 2013; Ishida et al, 2011). Based on our findings that CD4 + T cell responses were impaired in the absence of DLL4 on APCs, we posit that the immune-suppressive effects of DLL4 mAb in these models were due to less-efficient T cell priming.…”
Section: Discussionmentioning
confidence: 99%
“…This inflammation-mediated demyelination disease of the central nervous system (CNS) can be induced by immunization with myelin antigens, viral infection or transfer of autoreactive T cells. Genetic and pharmacological interference with Notch signalling, as well as administration of blocking antibodies against Notch receptors or Delta-like ligand 4 (DLL4), impeded progression of the disease, resulting in reduced clinical severity 74,75,84,91,92,[118][119] . The mechanisms by which blockage of Notch signalling ameliorates EAE are not fully understood and require further investigation.…”
Section: Box 2 | Notch and Autoimmune Diseasementioning
confidence: 99%
“…These IL-10 producing splenocytes may not affect TMEV-IDD. Our Delta4 study in TMEV-IDD also revealed that the number of infiltrating MNCs in spinal cord was decreased, and absolute cell numbers of IFN-γ-, TNF-α-and IL-10-producing cells were significantly reduced in mice treated with anti-Delta4 mAb in effector phase compared with control mice (Takeichi et al, 2010). On the other hand, the number of IL-17-producing cells tended to increase in mice treated with anti-Delta1 mAb rather than control mice treated with non-specific IgG.…”
Section: Discussionmentioning
confidence: 56%
“…We previously demonstrated that administration of anti-Delta4 mAb suppressed the development of TMEV-IDD (Takeichi et al, 2010). In the present study, we have investigated the role of Delta1 using a neutralizing anti-Delta1 mAb in the development of TMEV-IDD.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation